Authentic small houses of the twenties : illustrations and floor plans of 254 characteristic homes - Jones, Robert T. (Robert Taylor), 1884-1963 (Dover books on architecture, 1987)
Modestly priced, richly illustrated reprint of rare guidebook published by Architects' Small House Service Bureau. Designs, floor plans, construction materials, prices for wide variety of small homes. Over 800 line drawings and photographs.